Is insulin intoxication still the perfect crime? Analysis and interpretation of postmortem insulin: review and perspectives in forensic toxicology. (20th April 2020) - Bottinelli, Charline; Cartiser, Nathalie; Bévalot, Fabien; Fanton, Laurent; Guitton, Jérôme
Abstract: Insulin is an anabolic hormone essential to glucose homeostasis. Insulin therapy, comprising human insulin (HI) or biosynthetic analogs, is critical for the management of type-1 diabetes and many of type-2 diabetes. However, medication error including non-adapted dose and confusion of insulin type, and misuse, such as massive self-administration or with criminal intent, can have lethal consequences. The aim of this paper is to review the state of knowledge of insulin analysis in biological samples and of the interpretation of insulin concentrations in the situation of insulin-related death investigations. Analytic aspects are considered, as quantification can be strongly impacted by methodology. Immunoanalysis, the historical technique, has a prominent role due to its sensitivity and ease of implementation. Recently, liquid chromatography coupled to mass spectrometry has provided indispensable selectivity in forensic contexts, distinguishing HI, analogs, and degradation products. We review the numerous antemortem (dose, associated pathology, injection-to-death interval, etc.) and postmortem parameters ( in corpore degradation, in vitro degradation related to hemolysis, etc.) involved in the interpretation of insulin concentration. The interest and limitations of various alternative matrices providing a valuable complement to blood analysis are discussed. Vitreous humor is one of the most interesting, but the low diffusion of insulin in this matrix entails very low concentrations. Injection site analysis is relevant for identifying which type of insulin was administered. Muscle and renal cortex are matrices of particular interest, although additional studies are required. A table containing most case reports of fatal insulin poisoning published, with analytical data, completes this review. A logic diagram is proposed to highlight analytical issues and the main parameters to be considered for the interpretation of blood concentrations. Finally, it remains a challenge to provide reliable biological data and solid interpretation in the context of death related to insulin overdose. However, the progress of analytical tools is making the "perfect crime" ever more difficult to commit.